The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/brs.0000000000003156
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Posterior Cervical Foraminotomy as an Alternative to Anterior Cervical Discectomy and Fusion for Unilateral Cervical Radiculopathy

Abstract: Study Design. Systematic review and meta-analysis. Objective. The aim of this study was to evaluate clinical outcomes, complications, and reoperations of minimally invasive posterior cervical foraminotomy (MI-PCF) for unilateral cervical radiculopathy without myelopathy, in comparison to anterior cervical decompression and fusion (ACDF). Summary of Background Data. ACDF is a standard treatment for cervical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 32 publications
5
55
0
Order By: Relevance
“…The 12% complication rate of this cohort was comparable to other minimally invasive posterior cervical foraminotomy and anterior cervical discectomy and fusion literature [4,10,31,32]. The most common complications in the literature related to posterior cervical foraminotomy are wound issues, neuropraxia and durotomy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The 12% complication rate of this cohort was comparable to other minimally invasive posterior cervical foraminotomy and anterior cervical discectomy and fusion literature [4,10,31,32]. The most common complications in the literature related to posterior cervical foraminotomy are wound issues, neuropraxia and durotomy.…”
Section: Discussionsupporting
confidence: 56%
“…The most common complications in the literature related to posterior cervical foraminotomy are wound issues, neuropraxia and durotomy. PECD has good potential in decreasing wound related complications due to its ability to preserve soft tissue and avoid prolonged retraction of any particular cervical muscle group due to constant mobility of endoscope [31]. Incidental durotomy can be a problem in any endoscopic or open procedure, a patch blocking repair technique for small incidental dura tear is a common strategy in treatment of endoscopic dura tear [33].…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 30 A recent meta-analysis, with relatively short follow-up times, found greater improvement of radicular symptoms after foraminotomy, yet no difference in the reoperation rates between foraminotomy and ACDF. 34 …”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] These 2 references were used to compare the results for MI-PCF reported in Sahai's study. [ 10 ] The overlap in the 95% CIs of the 2 cohorts indicated there was no significant difference at the P < .05 level.…”
Section: Methodsmentioning
confidence: 99%
“…PECF has many advantages, including preserving discs and motion, avoiding graft-related complications and reducing adjacent segmental disease. Recently, Sahai et al [ 10 ] conducted a meta-analysis that compared minimally invasive PCF (PECF included) and ACDF, and the results showed that compared with ACDF, minimally invasive PCF may be effective and safe. To our knowledge, no meta-analysis study has previously been performed to compare outcomes between ACDF and PECF.…”
Section: Introductionmentioning
confidence: 99%